2000
DOI: 10.1289/ehp.00108205
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to infections and immune status in Inuit infants exposed to organochlorines.

Abstract: We investigated whether organochlorine exposure is associated with the incidence of infectious diseases in Inuit infants from Nunavik (Arctic Quebec, Canada). We compiled the number of infectious disease episodes during the first year of life for 98 breast-fed and 73 bottle-fed infants. Concentrations of organochlorines were measured in early breast milk samples and used as surrogates to prenatal exposure levels. Immune system parameters were determined in venous blood samples collected from infants at 3, 7, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(93 citation statements)
references
References 30 publications
3
89
0
1
Order By: Relevance
“…DDE, DDT's main metabolite, is one of the most ubiquitous toxins in foods. Prenatal exposure to DDT increases the risk of otitis media [35]; post-natal exposure to DDT has been linked to impairment of the upper respiratory tract immunity as evidenced by increased upper respiratory tract infections. It has been demonstrated that DDT diminished neutrophil functions and reduced mitogen-induced lymphocyte proliferation response [36].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…DDE, DDT's main metabolite, is one of the most ubiquitous toxins in foods. Prenatal exposure to DDT increases the risk of otitis media [35]; post-natal exposure to DDT has been linked to impairment of the upper respiratory tract immunity as evidenced by increased upper respiratory tract infections. It has been demonstrated that DDT diminished neutrophil functions and reduced mitogen-induced lymphocyte proliferation response [36].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…The toxic and immunomodulatory effects of POPs have previously been investigated, especially in relation to polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs) and perfluoroalkylated substances (PFASs) [35]. In addition, previous studies have reported the effects of POP exposure on the immune system in laboratory animals and humans, especially in connection with depressed immunity and reduced vaccination response [612]. Several biomarkers have been investigated in relation to POP exposure, in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This population has high exposure to PCBs and other organochlorines because of their high consumption of carnivorous fish and marine mammals. Various PCBs and DDE were measured in cord blood and/or maternal plasma at delivery (Dewailly et al, 2000;Dallaire et al, 2004) and in the infants' blood at follow-up (Dallaire et al, 2004). In both studies, the risk of otitis media during the first year of life increased with increasing prenatal exposure to PCBs and DDE (Dewailly et al, 2000;Dallaire et al, 2004), although most of the associations did not reach statistical significance.…”
Section: Consequences Of Exposuresmentioning
confidence: 99%
“…Various PCBs and DDE were measured in cord blood and/or maternal plasma at delivery (Dewailly et al, 2000;Dallaire et al, 2004) and in the infants' blood at follow-up (Dallaire et al, 2004). In both studies, the risk of otitis media during the first year of life increased with increasing prenatal exposure to PCBs and DDE (Dewailly et al, 2000;Dallaire et al, 2004), although most of the associations did not reach statistical significance. In the latter study, the risk of all infections combined was significantly increased with increasing prenatal PCB level (Dallaire et al, 2004).…”
Section: Consequences Of Exposuresmentioning
confidence: 99%
See 1 more Smart Citation